STUDI PENGGUNAAN BAHAN AJAR AKUNTANSI KELAS XAKUNTANSI SMK NEGERI 10 SURABAYA - ISTIANAH (Program Studi Pendidikan Akuntansi Fakultas Ekonomika dan Bisnis Universitas Negeri Surabaya, 2013)
Teaching material is important role in the learning process, for it carried out research that aims to know what teaching material used by accounting teachers in class X Accounting SMK Negeri 10 Surabaya for the accounting cycle of service company and to know the reason of teachers use that teaching material in accounting learning activities in the classroom. This research is descriptive research. Research done by the SMK Negeri 10 Surabaya with the research subject is accounting teacher of class X. Technique of data collection is using interviews and documentation. Feasibility of teaching material, the result that teachers use cast teaching material which the title “ Akuntansi 1, Siklus Akuntansi Perusahaan Jasa dan Dagang” publisher by Yudhistira, year 2011, it show that the teaching material is very fit for used in the accounting learning activities of class X Accounting with percentage is 86,2%. Keyword : teaching material, descriptive research, accounting cycle of services company